Pengaruh Total Quality Management dan Supply Chain Management terhadap Kinerja Operasional UMKM Makanan dan Minuman di Kota Cimahi - Neng Rifka Khoirunnisa; Elis Dwiana Ratnamurni (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze the influence of Total Quality Management (TQM) and Supply Chain Management (SCM) on the operational performance of food and beverage MSMEs in Cimahi City. The research method used a quantitative approach with a convenience sampling technique of 100 respondents, owners or managers of food and beverage MSMEs in Cimahi City. Data were collected through questionnaires and analyzed using multiple linear regression methods with the aid of validity and reliability tests, and classical assumption tests. The results show that Total Quality Management (TQM) has a positive and significant effect on operations with a t-value of 2.889 and a significance level of 0.005, and Supply Chain Management (SCM) also has a positive and significant effect on operations with a t-value of 4.023 and a significance level of 0.000. Simultaneously, TQM and SCM significantly influence operational performance with an F-value of 21.336 and a significance level of 0.000, contributing 30.6% to MSME operational performance. The conclusion of this study indicates that optimal application of Total Quality Management and Supply Chain Management principles can improve the operational performance of food and beverage MSMEs in Cimahi City. Keywords: Supply Chain Management, Operational Performance, Operational Management